A ratio fluorescence method based on dual emissive gold nanoclusters for detection of biomolecules and metal ions. Issue 19 (20th April 2022) - Kong, Chenchen; Luo, Yunjing; Zhang, Wei; Lin, Taifeng; Na, Zhen; Liu, Xuemei; Xie, Ziqi
Abstract : Novel dual-emissive gold nanoclusters (d-Au NCs) were prepared and applied for the simultaneous detection of phenylalanine or Fe 3+ . Abstract : Gold nanoclusters have good biocompatibility and can be easily modified to improve their luminescence properties. In this study, we prepared a new type of dual-emitting gold nanoclusters (d-Au NCs) for discriminative detection of phenylalanine and Fe 3+ with high selectivity and sensitivity. The fluorescence sensor which was synthesized without any further assembly or conjugation shows dual-emissions at 430 nm and 600 nm under a single excitation at 350 nm. Phenylalanine can turn on the red emission of the probe, while Fe 3+ can turn on its yellow emission and turn off the red emission. By detecting a variety of amino acids and metal ions, d-Au NCs showed good selectivity to phenylalanine and Fe 3+ . Finally, this method was applied to determine phenylalanine and Fe 3+ in lake water, human urine and milk, which has certain application prospects in the field of biology and environment.